2019
DOI: 10.1016/j.envpol.2018.10.077
|View full text |Cite
|
Sign up to set email alerts
|

The use of gene expression to unravel the single and mixture toxicity of abamectin and difenoconazole on survival and reproduction of the springtail Folsomia candida

Abstract: Pesticides risk assessments have traditionally focused on the effects on standard parameters, such as mortality, reproduction and development. However, one of the first signs of adverse effects that occur in organisms exposed to stress conditions is an alteration in their genomic expression, which is specific to the type of stress, sensitive to very low contaminant concentrations and responsive in a few hours. The aim of the present study was to evaluate the single and binary mixture toxicity of commercial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The fungicide Score 250 EC® had no effects on F. candida at both temperatures tested (23 and 33°C). Oliveira et al (2018) determined an EC 50 for F. candida of this compound of 28.9 mg a.s./kg soil. F. candida was clearly less sensitive to difenoconazole than to abamectin.…”
Section: Figmentioning
confidence: 98%
See 3 more Smart Citations
“…The fungicide Score 250 EC® had no effects on F. candida at both temperatures tested (23 and 33°C). Oliveira et al (2018) determined an EC 50 for F. candida of this compound of 28.9 mg a.s./kg soil. F. candida was clearly less sensitive to difenoconazole than to abamectin.…”
Section: Figmentioning
confidence: 98%
“…Previous studies revealed a rather large variation in the toxicity of abamectin to collembolans. Oliveira et al (2018), for example, noted a 50% reduction in F. candida when exposed to 0.06 mg a.s./kg in a natural Brazilian soil (15% organic matter content; CEC 3.33 (meq/ 100 g); 48% clay; 12% silt; and 19, 11, and 10% of fine, medium, and coarse sand, respectively) in the laboratory. However, Diao et al (2007) reported such a reduction at a ten-fold higher concentration in a natural (York, England) sandy-loamy soil (21% clay, 12% silt, 67% sand, 2.22% organic carbon and a pH of 7.0) (EC 50 F. candida = 0.68 mg a.s./kg).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Fipronil is an insecticide of contact and ingestion, belonging to the chemical group of the pyrazoles, indicated for an extensive range of applications from plants to animals (EC, 2011;Brasil, 2020). Studies demonstrating the ecotoxicological potential of pesticides on non-target species, such as bees, earthworms and collembolans, include the death of these individuals, possibly leading to a population decline, even at recommended or very low concentrations (Pitombeira de Figueirêdo et al, 2019;Sánchez-Bayo et al, 2016;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%